Possibilities of Robot Programming Education in Offline and Online Environments - Pántya, Róbert; Novák, Tamás; Mucsics, F. László (Acta Carolus Robertus, 2023)
In the spring of 2020, the Covid-19 pandemic situation put everyone in a particularly difficult situation in all areas of life. Those working in education had to implement their courses online overnight, which until then had been mostly, or even exclusively, offline in the classroom. This challenge also put colleagues teaching robot programming in a difficult situation. At the Károly Róbert Campus and its predecessor institutions, we have been dealing with students studying information technology for almost a decade and a half. We teach subjects related to robotics as optional subjects in the Business Informatics BSc course launched in 2010, and as compulsory subjects in the higher education program for Computer Science running since 2019.In our study, we compare the robotics education implemented in the higher education program for Computer Science in an online and offline environment. We present in detail how the subjects „Methodological Basics of Programming” (first semester) and „Basics of Robotics” (third semester) were implemented before (offline) and during (online) the Covid-19 pandemic. At the end of our investigations, we make conclusions and suggestions about the most important actions after the end of the epidemic situation, how we can prepare with our subjects taught for the situation, if everyday life and the educational environment were to change similarly drastically.
Keywords: robotics; programming; e-learning